PERILAKU PEMBELIAN PRODUK DAN PENGGUNAAN KREDIT PADA GENERASI Z DI PLATFORM MEDIA SOSIAL - Rohmah, Allika Arisandy Nur; Lupita, Aprilia; Zahra, Fhadilla; Hatimatunnisani, Hani; Keizer, Hendriady de (Jurnal Sosio dan Humaniora (SOMA), 2025)
This study aims to analyze product purchasing and credit usage behavior in Generation Z exposed to social media. Generation Z is known for their high activity on platforms such as TikTok, Instagram, and X (Twitter), which serve not only as entertainment sources but also influence their consumption decisions. Using a descriptive quantitative approach, data were collected from 50 respondents through an online questionnaire. The results show that respondents' interest in purchasing products on social media is quite high with the main driving factors being personal needs, discounts and promotions. Shopee PayLater is a fairly popular service platform, although its usage level is still relatively low due to considerations of caution regarding debt risks. Although responses regarding the level of influence of social media vary, the platform still plays a role in shaping Generation Z's shopping habits. So there is a need for better financial literacy so that Generation Z can use credit wisely and avoid excessive consumer behavior.